2(5x-4)=6x+12

Simple and best practice solution for 2(5x-4)=6x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x-4)=6x+12 equation:


Simplifying
2(5x + -4) = 6x + 12

Reorder the terms:
2(-4 + 5x) = 6x + 12
(-4 * 2 + 5x * 2) = 6x + 12
(-8 + 10x) = 6x + 12

Reorder the terms:
-8 + 10x = 12 + 6x

Solving
-8 + 10x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + 10x + -6x = 12 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-8 + 4x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + 4x = 12 + 0
-8 + 4x = 12

Add '8' to each side of the equation.
-8 + 8 + 4x = 12 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = 12 + 8
4x = 12 + 8

Combine like terms: 12 + 8 = 20
4x = 20

Divide each side by '4'.
x = 5

Simplifying
x = 5

See similar equations:

| -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 | | 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x | | 3(50+25)= | | 19y=76 | | 4.87=m+0.87 | | 3(x-6)=9(x-2) | | 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 | | 63=-15+x |

Equations solver categories